PENGARUH PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING DAN PAIR CHECKS TERHADAP HASIL BELAJAR SISWA PADA MATERI BANGUN RUANG SISI DATAR - Muawanah, Lina (Universitas Muhammadiyah Ponorogo, 2023)
This study is motivated by the low mathematics learning outcomes, one of the reasons being that students have a poor grasp of the material on flat-sided geometric shapes due to inappropriate teaching methods. Teachers tend to emphasize concepts based on memorization and have not yet implemented suitable learning models. The purpose of the research is to determine whether there is a difference in the learning outcomes of flat-sided spatial shapes material among eighth-grade students at SMP N 1 Suruh with the application of the guided discovery learning model (PT) and pair check. (PC). The research uses a quantitative approach with a type of Quasi-Experimental research and a Posttest-Only Control Group Design. The sampling technique employs Nonprobability Sampling with Purposive Sampling, involving class VIII A and D with a total of 83 students applying the PC learning model, and class VIII B and F with a total of 85 students also applying the PC learning model. Data collection techniques include tests and documentation. The data analysis technique in this study uses the T-test. The research results indicate that there is a difference in learning outcomes for flat-sided spatial shapes with the application of the PT and PC learning models. The average learning outcomes using the PT learning model are better than those using the PC learning model.